The pathophysiology of acid-base changes in chronically phosphate-depleted rats: bone-kidney interactions. - Emmett, M (1977)
Acid-base disturbances may develop secondary to the changes in renal tubular function and bone dynamics which attend phosphate depletion (PD). This work characterizes the acid-base status of rats fed a low phosphate diet. After 18 days, PD rats had marked calciuria (pair-fed controls: 0.3 +/- 0.2; PD 32.2 +/- 2.5 mueq/h; P less than 0.001), severe bicarbonaturia (controls: 0; PD 17.6 +/- 0.2 meq/h; P less than 0.001), and negative net acid excretion (controls: 44.5 +/- 2.9; PD: --6.6 +/- 2.5 meq/h; P less than 0.001), but plasma pH, HCO3, and PCO2 were equal in both groups. After 45 days, plasma HCO3 fell to 21.1 +/- 0.9 meq/liter in PD (controls: 23.6 +/- 0.5 meq/liter; P less than 0.05), while bicarbonaturia (controls: 0.4 +/- 0.2; PD: 3.8 +/- 1 mueq/h; P less than 0.02) and calciuria were present but diminished. These data suggested the coexistence of bone HCO3 mobilization and renal HCO3 wasting in PD. To test this thesis, bicarbonaturia was eliminated by nephrectomy. 24 h later plasma HCO3 was higher in PD rats (controls: 19.3 +/- 0.02; PD: 22.6 +/- 0.8 meq/liter; P less than 0.05), consistend with the presence of extrarenal HCO3 production. After inhibition of bone resorption with colchicine (1 mg/kg), plasma HCO3 decreased to 16.8 +/- 0.6 meq/liter in PD rats (controls): 26.4 +/- 1 meq/liter; P less than 0.001) while bicarbonaturia persisted. These data indicate that the plasma HCO3 in PD is the net result of renal HCO3 wasting and bone HCO3 mobilization. These combined effects maintain normal blood HCO3 initially (18 days) but with time (45 days), bone resorption diminishes and the acidifying renal tubular defect predominates.